Obesity An overview of the complex biological effects of expanding adipose tissue - T.W. van Haeften (JURNAL WIDYA MEDIKA, 2013)
Obesity has a more complex biology than previously thought. Feeding behaviour is regulated via a integrative circuit of afferent input from the stomach, the pancreas and the intestines via hormonal influences and the vagal nerve, which affect hypothalamic nuclei. This will lead to satiety and inhibition of hunger combined with other effects such as energy expenditure and growth promoting effects. Moreover, upon sufficient caloric intake, triglycerides are taken up in adipocytes, which in their turn will produce more leptin which inhibits hypothalamic nuclei and which will add to these hypothalamic effects. It has been suggested that more macrophages enter the adipose tissue which would alter adipocyte secretion. Adipocytes are now known to produce an array of proteins with hormonal effects calledadipo(cyto)kines. In obesity, many of these adipokines are produced in substantially higher amounts with potentially deleterious effcets notably on the risk of atherosclerosis, type 2 diabetes and cancer.